Analysis of Rayleigh, Rician and Nakagami-m fading channel using Matlab Simulation - Mrs. Anita Chopra2, Yashraj Singh1 (International Journal of Engineering Technology and Computer Research, 2015)
The fading, which is caused due to multipath propagation in a communication channel, challenges the wireless communication engineer who tries to establish a reliable communication path between transmitter and receiver. An effort has been made to demonstrate the comparison of the Rayleigh , Rician and Nakagami fading channel models by using MATLAB simulation in terms of source velocity and probability density function. We have developed algorithms for above channel, which calculate the Reference signal, Inphase signal ,Quadrature Signal, Envelope Signal, Probability density function . These parameters has play very important role in the performance analysis and design of the digital communication systems over the multipath fading environment.. Keywords: wireless Communication, Rayleigh fading, Rician fading, Nakagami-m fading channel.